Exportaciones chinas y mexicanas hacia Estados Unidos: ¿sigue China afectando a México? - CABRANES MÉNDEZ, Flora (Papeles de Europa, 2011)
The success of China as a leading exporter and its growing importance in the U.S. market has negatively affected trade of countries such as Mexico, with highly concentrated exports to the United States and with an export structure similar to the one of China. However, in 2004-2009 there have been some signs of recovery in the Mexican exports to that market. This paper addresses this issue by comparing the evolution of Chinese and Mexican exports to U.S., for then examine whether the Mexican recovery is due to changes in the competition degree between the products of both countries or to other factors.
Keywords: China; Mexico; U; S; market; Exports; Competitiveness; Trade competition